Preventive Transcendental Of Mass Violence Crimes - Purwadi Wahyu Anggoro (Journal of Transcendental Law, 2019)
ABSTRACT Objectives: This article aims to explain the causes of criminal acts of violence that occur in cases of violence involving the masses and explicate the concept of preventing violent crimes involving masses who have a transcendental paradigm. Methodology: This research was qualitative nondoctrinal research. The strategy of applying Preventive Law with a Transcendental paradigm as a concept of preventing criminal acts of mass violence with religious nuances is as a way to reduce the emotions of the masses and eliminate the intention of the masses to commit acts of violence. The sources of data were in the form of research and interviews of cases of mass violence. The data analysis used interpretation techniques based on the (premise) stage of mass violence, according to Niel Smelser and transcendental preventive patterns in accordance with the literature reviews of books and scientific journals. Results: The results showed that violence is an act against the law (onrechtmatige daad), where it is the human state of nature. In the crowd, people will imitate other people's actions, lose control, and take aggressive actions. The law is a tool for social engineering to prevent crime, maintain an orderly society, and provide protection for citizens. Law enforcement is prioritized using soft methods (the soft hand of society) to prevent violence from happening with a transcendental paradigm approach to restoring human nature, according to Surah Ali Imran (3) paragraph 110, namely amar ma'ruf, which contains transcendental ethical values. Functions: This research is useful in the implementation of the Transcendental Preventive Law for law enforcement officers, in this case, the National Police, as an effort to break the 4th stage, namely the stage before triggering incidents occur. It is intended that at the time of mass violence, the Preventive Transcendental Law can cool down the emotions of the masses while at the same time restore human awareness that peace, compassion, and the world and its contents are a gift that must be accountable to God Almighty. Originality/Novelty: Transcendental Preventive Law is an effort to prevent violent crime in mass violence that is based on transcendental principles, by giving a religious touch to remind the masses that violence is a sinful act and to remind the existence of God Almighty.